Social fragmentation and territorial planning (2007)
A closer approach to the current phenomenon, that is the social fragmentation starting from a global transformation, needs to explicit whit its meaning and its manifestations among the economic, political and sociocultural ambits; regarding the social ambit, the individual logics must be emphasized; the political ambit the incidence of fragmented social practices concerning the territorial planning and the socio-cultural ambit the deprived –land possession dynamics. Thus, the 3 ambits are used as analytical foundation to be explicit with the most significant implications, which link the social fragmentation to the territorial planning. Also is necessary to understand the territorial planning like socio-politic process permit to analysis participative practices. The above information intention is to ponder on those reflections to expand and up date the knowledge regarding the economic, political and socio-cultural and ambits in this contemporary world.